3-E analysis and optimization of an organic rankine flash cycle integrated with a PEM fuel cell and geothermal energy. (13th January 2020) - Li, Zhixiong; Khanmohammadi, Shoaib; Khanmohammadi, Saber; Al-Rashed, Abdullah A.A.A.; Ahmadi, Pouria; Afrand, Masoud
Abstract: The current research deals with thermodynamic and economic analyses and optimization of a geothermal system integrated with organic Rankine flash cycle (ORFC) and a polymer electrolyte membrane fuel cell (PEM-FC). A thermodynamic model for ORFC and PEM-FC is developed to investigate employing the PEM-FC in a combined geothermal ORFC. A comparative study is carried out to determine the effect of applying PEM-FC in a geothermal based ORFC. The validation of PEM-FC simulation with experimental data from the literature shows a good agreement. The results of numerical modeling indicate that using the rejected heat in the PEM-FC instead of the low-temperature geothermal source can increase the net output power from 254.9 kW to 1628.9 kW and the exergy efficiency from 23.77% to 36.19%, in the case of R123 as working fluid for the ORC system. Furthermore, using the PEM-FC imposes 9.07 US/h cost rate to the system. Additionally the parametric study shows that the net output power and the total cost rate of the system are two major objective functions for the optimization. Thus, a multi-objective genetic algorithm is applied to determine the optimal values of design parameters with respect to some practical constraints. The results of the multi-criteria optimization represent that the optimum value of decision variables with considered objective functions are T 1 = 116 °C, r f l a s h = 0.55, P F C = 230 kPa, and P 4 = 1208.4 kPa . Graphical abstract: Image 1 Highlights: Thermodynamic conceptualization of the geothermal energy integrated with a PEM-FC. R123 regarding the cost rate and exergy efficiency is the best working fluid. Exergy efficiency of the integrated system with employing PEM-FC increase 18.68%. In the optimum state of the Geo/ORFC-FC system, the net output work is 1571.1 kW. In the optimum state of the Geo/ORFC-FC system, the total cost rate is 10.51 US/h.